Introduction to Multimodal Social Semiotics and Analysis of Educational Contexts - Flores Solano, Carol (2020)
This introduction to social semiotics and multimodality outlines the connection between both disciplines for use in a multimodal social semiotic theoretical framework. Five possible research options are examined under this focus to analyze school interactions. Multimodality is often conceptualized imprecisely as a new type of text, textual products generated through the use of technology or a pedagogical perspective for designing educational activities. Given this broad disciplinary spectrum, the scarcity of related publications in Spanish and the growing number of studies applicable to this framework in the field of education this articles addresses the advantages of multimodal social semiotics for analyzing semiosis in educational settings.